Why Not Better and Cheaper? Healthcare and Innovation - Skinner, Jonathan (Journal of Economic Literature, 2024)
Jonathan Skinner of Dartmouth University reviews “Why Not Better and Cheaper? Healthcare and Innovation” by James B. Rebitzer and Robert S. Rebitzer. The Econlit abstract of this book begins: “Considers why the US health-care system is becoming neither better nor more affordable over time, contending that the health sector generates the wrong kinds of innovation by making it easy to profit from low-value innovations and difficult to do the same from innovations that reduce care costs.”